2019
DOI: 10.1063/1.5125788
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties and interface abruptness of AlSiO gate dielectric grown on 0001¯ N-polar and (0001) Ga-polar GaN

Abstract: The electrical properties and the interface abruptness of aluminum silicon oxide (AlSiO) dielectric grown in situ on 0001¯ N-polar and (0001) Ga-polar GaN by metal organic chemical vapor deposition were studied by means of capacitance-voltage (CV) and atom probe tomography (APT) measurements. The growth of AlSiO on N-polar GaN resulted in a positive flatband voltage shift of 2.27 V with respect to that on Ga-polar GaN, which exemplifies the influence of the GaN surface polarization charge on the electrical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…4 with the increase of working gas pressure, which is quite opposite to the sputtering current increasing trend. The relationship between sputtering voltage (V) and current (I) at a constant sputtering power (P) with the variation of working gas pressure can be calculated using (2).…”
Section: B Variation In DC Magnetron Sputtering Current and Voltagementioning
confidence: 99%
“…4 with the increase of working gas pressure, which is quite opposite to the sputtering current increasing trend. The relationship between sputtering voltage (V) and current (I) at a constant sputtering power (P) with the variation of working gas pressure can be calculated using (2).…”
Section: B Variation In DC Magnetron Sputtering Current and Voltagementioning
confidence: 99%
“…Aluminum silicon oxide (AlSiO) has been proposed as a high-quality and reliable gate dielectric for GaN-based devices [17][18][19]. Alloying of Al 2 O 3 with silicon to form amorphous AlSiO has the potential to incorporate the advantages of both SiO 2 (E g = 9.0 eV) and Al 2 O 3 (E g = 6.7 eV) thus realizing high band offsets and high breakdown strength [18,20]. A low interface states (D it ) of ∼10 12 cm −2 eV −1 was achieved in AlSiO on Ga-polar GaN using metal-organic chemical vapor deposition (MOCVD) technique and a dielectric lifetime of 20 years for electric fields higher than 3 MV cm −1 was predicted by Chan et al [17,21].…”
Section: Introductionmentioning
confidence: 99%
“…A low interface states (D it ) of ∼10 12 cm −2 eV −1 was achieved in AlSiO on Ga-polar GaN using metal-organic chemical vapor deposition (MOCVD) technique and a dielectric lifetime of 20 years for electric fields higher than 3 MV cm −1 was predicted by Chan et al [17,21]. Sayed et al studied the impact of GaN polarity and the effect of post-metallization annealing (PMA) on the electrical properties of AlSiO/Npolar GaN MOS devices [20,22,23]. Annealing in air ambient at 370 • C was reported to reduce the density of near-interface traps by a factor of two from 5.6 × 10 11 to 2.6 × 10 11 cm −2 [23].…”
Section: Introductionmentioning
confidence: 99%
“…Kikuta et al and our group demonstrated that the post-deposition annealing of PEALD-deposited AlSiO and the post-metallization annealing of MOCVD-grown AlSiO, respectively, can further improve the bulk and interfacial properties of AlSiO resulting in improved operation stability [16,17]. Recently, we showed that the GaN polarity can impact the electrical and interfacial properties of AlSiO metal oxide semiconductor (MOS) devices by demonstrating that the growth of AlSiO (with a silicon composition of 7%) on Npolar GaN resulted in a positive flat-band shift and sharper interface with respect to AlSiO grown on Ga-polar GaN [18]. The exceptional performance of GaN transistors based on the N-polar technology for high-frequency and voltage-switching applications [19][20][21] motivated this investigation towards the understanding of the role of the silicon composition in AlSiO for future use in the gate stack of next-generation N-polar GaN-based transistors.…”
Section: Introductionmentioning
confidence: 99%